A comparative assessment of the aridity indices for analysis of the hydrothermal conditions. (October 2018) - Voropay, N N; Ryazanova, A A
Abstract: Comparison between hydrothermal coefficient of Selyaninov (HTC), Ped` drought index (Si ) and indices SPI, SPEI are presented. Indices were calculated for the territory of Southern Siberia (50-65 N, 60-120 E). Functionality of the web-GIS "CLIMATE" was extended by a software module based on the integrated package to calculate indices. The ECMWF ERA-Interim reanalysis data on air temperature and precipitation were used as input data for the study. Analysis were carried out for the warm season from 1979 to 2017. The highest coefficients of linear correlation were obtained by comparing SPI and SPEI (0.8-0.9), Si and HTC (0.7-0.9) from June to August. Distribution of the number of strong and extreme droughts over the study period according to SPI and SPEI indices is the same, 2-3 strong droughts was observed per period. According to the analysis of Si, the highest frequency of strong droughts (up to 4) was observed also in July and August. But it was recorded only at the Sayan Mountains region. According to the results of the anomaly of HTC analysis, June and August are most droughty (2-3 strong droughts per period). The identified intensity and duration of droughts, based on these indices do not always coincide.